2012
DOI: 10.7314/apjcp.2012.13.5.2021
|View full text |Cite
|
Sign up to set email alerts
|

Loss of DBC2 Expression is an Early and Progressive Event in the Development of Lung Adenocarcinoma

Abstract: Purpose: DBC2 (Deleted in Breast Cancer 2) has been indicated to be a tumor suppressor gene in many cancers including lung adenocarcinoma recently. In this study, we aimed to explore the expression status of DBC2 in different subtypes of lung adenocarcinoma (from pre-invasive to invasive lesions), and to determine if downregulation becomes more marked with pathological progression. Methods: We collected 172 tissue samples from different subtypes of lung adenocarcinoma and investigated the frequency of DBC2 los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Subsequent studies further found that DBC2 expression was suppressed in approximately 60% of breast cancers, 50 to 70% of lung cancers, and 75% of bladder cancers [4], [14], [15]. Loss of DBC2 expression in bladder and breast cancer was associated with aberrant methylation of the gene's promoter [14], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies further found that DBC2 expression was suppressed in approximately 60% of breast cancers, 50 to 70% of lung cancers, and 75% of bladder cancers [4], [14], [15]. Loss of DBC2 expression in bladder and breast cancer was associated with aberrant methylation of the gene's promoter [14], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…RhoBTB2, for example, was reported to be homozygously deleted in a large percentage of breast cancer tumors (Hamaguchi et al 2002;Mao et al 2009). Downregulation of RhoBTB2 was further observed in lung, bladder, bone and gastric cancer (Cho et al 2009;Shi et al 2008;Dong et al 2012;Jin et al 2013). Obtained in breast cancer cells, evidence suggests that RhoBTB2 exerts a tumor-suppressive function by inhibiting cancer cell proliferation, migration and invasiveness (Ling et al 2014;Mao et al 2011).…”
Section: Rhobtb Lkb1 (Stk11) Hippo Pathway Ubiquitinationmentioning
confidence: 92%
“…Consistent with roles as tumor suppressors, expression of all three RHOBTB genes has been found reduced or extinguished in a variety of tumor types. Expression of RHOBTB2 , the first member of the family to be proposed as a candidate tumor suppressor gene, has been found decreased in breast [ 6 , 24 , 25 ], lung [ 26 ], bladder [ 27 , 28 ], and stomach [ 29 ] cancers, in osteosarcomas [ 30 ], as well as in cell lines derived from breast, lung [ 6 ], and bladder [ 27 ] tumors, and HNSCCs (head and neck squamous cell carcinomas) [ 31 ]. Very often the degree of expression correlates with the primary location, grading, staging, or other features of the tumor.…”
Section: Rhobtbs As Tumor Suppressorsmentioning
confidence: 99%